Pembatalan Perkawinan dalam Sistem Hukum Indonesia: Analisis Regulasi, Faktor Penyebab, dan Dampaknya - Yerry Andro Foza; Enang Suyatna; Suhibbullah Suhibbullah; Rizal Tahsin; Azwar Hanas (An-Nisa: Journal of Islamic Family Law, 2025)
Marriage annulment is a legal measure taken to declare a marriage invalid and considered never to have occurred. In Indonesia, marriage annulment is regulated under Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). This study aims to analyze the factors leading to marriage annulment, the applicable legal procedures, and its impact on the parties involved, including the husband, wife, children, and shared assets. Based on legal analysis and case studies, the main causes of marriage annulment include improper marriage guardianship, violations of marriage procedures, and polygamous marriages conducted without the consent of the first wife and without court approval. Court rulings on marriage annulments have far-reaching legal implications, including the nullification of marital status, legal protection for children, and the division of shared assets. This study concludes that although regulations regarding marriage annulment are clearly defined, challenges remain in their implementation, particularly in law enforcement and public awareness of legal marriage requirements. Therefore, strengthening regulations, enhancing judicial oversight, and increasing legal education for the public are necessary to ensure that all marriages comply with the prevailing legal provisions.